(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the problem of emotional leadership within the managerial activities of managers. It is given the formula for effective interaction of such psychological phenomena as emotional leadership, social mobility and self-realization of personality. It is analyzed a regression model, where the effectiveness of the leader’s interaction with society depends on personal factors related to the level of selfawareness, self-control, ability to empathize and social skills. It is revealed the components of emotional leadership and defined their features in the context of the managerial activities of managers. It is determined the main characteristics of leader with developed emotional intelligence. The importance of emotional intelligence in the managerial activities of modern leaders is analyzed